2009
DOI: 10.2131/jts.34.129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of restricted feeding on blood parameters in pregnant rabbits

Abstract: -The effects of restricted feeding (20 g/day from gestational day (GD) 6 to 28) on pregnancy outcome and blood parameters were examined in pregnant rabbits. As compared with the group which was allowed free access to diet throughout the gestational period (NT group), the group subject---ulation and anti-coagulation factors. Moreover, abortions occurred in about half of the animals of the R group between GDs 23 and 27. When aborted rabbits were compared with those which could maintain pregnancy under restricted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Previous studies have reported that markedly restricted feed intake (20 g/d) resulted in embryo-foetal World rabbit sci. 23: 1-8 death, probably due to progesterone reduction, and lower foetal body weight (Matsuoka et al, 2009 and. In our study, the non-pregnant rabbits were excluded 10 d after AI and no caesarean sections or ultrasound examinations were performed.…”
Section: Productive Performancementioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies have reported that markedly restricted feed intake (20 g/d) resulted in embryo-foetal World rabbit sci. 23: 1-8 death, probably due to progesterone reduction, and lower foetal body weight (Matsuoka et al, 2009 and. In our study, the non-pregnant rabbits were excluded 10 d after AI and no caesarean sections or ultrasound examinations were performed.…”
Section: Productive Performancementioning
confidence: 96%
“…Other authors reported high body weight loss during pregnancy, but their experimental protocols included more severe and/or more long-lasting dietary restrictions, such as 20 g/d (Matsuoka et al, 2009) or 13 d of restriction (Cappon et al, 2005). Nafeaa et al (2011) found no decrease in body weight in pregnant does subjected to restriction (111 g/d) for the 1 st half of pregnancy, but significant losses with feed reduction during the 2 nd half of gestation.…”
Section: Body Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that pregnant rabbits subjected to restricted feeding of 20 g/day showed significant changes in the blood coagulation system suggesting a tendency to bleed and a clear decline in serum progesterone concentrations on gestation day 22 (GD 22), and that half of them showed blood progesterone concentrations less than 4.0 ng/ml which resulted in abortions on and after GD 23 (Matsuoka et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…
ABSTRACT -In our previous study on the effects of restricted feeding on pregnant rabbits (Matsuoka et al, 2009), animals given 20 g/day of diet on and after gestation day 6 (GD 6) showed significant changes in blood coagulation-related parameters suggesting a tendency to bleed and a decrease in serum concentration of progesterone, an important factor to maintain pregnancy, on GD 22, and a half of them showed serum progesterone concentrations less than 4.0 ng/ml which resulted in abortions on and after GD 23. In the present study, the effects of restricted feeding of 20 g/day from GD 6 to GD 22 on embryo-fetal and placental development on GD 23 as well as on blood coagulation-related parameters and serum progesterone concentrations on GD 22 were examined in pregnant rabbits.
…”
mentioning
confidence: 99%